Applications of Biomechanical Foot Models to Evaluate Dance Movements Using Three-Dimensional Motion Capture: A Review of the Literature. Issue 2 (June 2022) - Veirs, Kimberly P.; Fagg, Andrew H.; Haleem, Amgad M.; Jeffries, Lynn M.; Randall, Ken; Sisson, Susan B.; Dionne, Carol P.
Dance movement requires excessive, repetitive range of motion (ROM) at the foot-ankle complex, possibly contributing to the high rate of injury among dancers. However, we know little about foot biomechanics during dance movements. Researchers are using three-dimensional (3D) motion capture systems to study the in vivo kinematics of joint segments more frequently in dance-medicine research, warranting a literature review and quality assessment evaluation. The purpose of this literature review was to identify and evaluate studies that used 3D motion capture to analyze in vivo biomechanics of the foot and ankle for a cohort of dancers during dance-specific movement. Three databases (Pub Med, Ovid MEDLINE, CINAHL) were accessed along with hand searches of dance-specific journals to identify relevant articles through March 2020. Using specific selection criteria, 25 studies were identified. Fifteen studies used single-segment biomechanical foot models originally created to study gait, four used a novel two-segment model, and six utilizeda multi-segment foot model. Nine of the studies referenced common and frequently published gait marker sets and four used a dance-specific biomechanical model with purposefully designed foot segments to analyze the dancers' foot and ankle. Description of the biomechanical models varied, reducing the reproducibility of the models and protocols. Investigators concluded that there is little evidence that the extreme total, segmental, and intersegmental foot and ankle ROM exerted by dancers are being evaluated during dance-specific movements using 3D motion capture. Findings suggest that 3D motion capture is a robust measurement tool that has the capability to assist researchers in evaluating the in vivo, intersegmental motion of the foot and ankle to potentially discover many of the remaining significant factors predisposing dancers to injury. The literature review synthesis is presented with recommendations for consideration when evaluating results from studies that utilized a 3D biomechanical foot model to evaluate dance-specific movement.